2014
DOI: 10.2500/ajra.2014.28.4023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Olfaction in Patients with Pemphigus Vulgaris

Abstract: PV causes olfactory dysfunction leading to eventual hyposmia that decreases quality of life. We suggest that olfactory testing be included in PV evaluation for the diagnosis and treatment of hyposmia, when necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In the present study 50% of patients with postinfectious olfactory loss showed ANAs. These results suggest that postinfectious smell loss might be related to immune mediated processes as reduced olfactory function has been already shown in several autoimmune meditaed diseases such as multiple sclerosis (27) , pemphigus vulgaris (10) , psoriasis vulgaris (11) and Sjögren syndrome (12) .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study 50% of patients with postinfectious olfactory loss showed ANAs. These results suggest that postinfectious smell loss might be related to immune mediated processes as reduced olfactory function has been already shown in several autoimmune meditaed diseases such as multiple sclerosis (27) , pemphigus vulgaris (10) , psoriasis vulgaris (11) and Sjögren syndrome (12) .…”
Section: Discussionsupporting
confidence: 59%
“…In several autoimmune diseases (8) decreased olfactory function has been shown, e.g. systemic lupus erythematosus (9) , pemphigus vulgaris (10) , psoriasis vulgaris (11) , Sjögren syndrome (12) and Wegener's disease (13,14) . In addition, reduced olfactory function has been shown in several other diseases, which are discussed to be mediated by autoimmune processes, e.g.…”
Section: Neurological Disorders and Autoimmune Processes Have Beenmentioning
confidence: 99%
“…Regarding the response to treatment of NT involvement in PV, several studies have confirmed that systemic treatment is highly effective . Recovery of mucosal lesions is practically complete although recently, some rare cases of secondary epiglottis synechiae, or olfactory dysfunction have been reported . Secondary infection on NT mucosa might play a role in secondary and local fibrosis.…”
Section: Nt Involvement In Pvmentioning
confidence: 99%
“…2,3,[8][9][10][11][12] Recovery of mucosal lesions is practically complete although recently, some rare cases of secondary epiglottis synechiae, 18 or olfactory dysfunction have been reported. 19 Secondary infection on NT mucosa might play a role in secondary and local fibrosis. As a positive correlation has been detected between the duration of PV and the severity of NT involvement, 11 delay in beginning treatment may also lead to fibrous bands on NT mucosas.…”
Section: Nt Involvement In Pvmentioning
confidence: 99%
“…Meric et al 15 describe the relationship between pemphigus vulgaris and nasal inflammatory disease, demonstrating that these patients are more likely to exhibit nasal lesions and dysfunction of both odor threshold and identification. These findings underscore roles for nasal examination and olfactory evaluation in patients with this autoimmune disease.…”
mentioning
confidence: 99%